"As planning is everything, it is good for something!" A Coasian economic taxonomy of modes of planning. (August 2016) - Lai, Lawrence WC
Against two extreme forms of thinking, which have influenced planning theory, this article argues, in the context of a looming amount of literature generated in a movement for private planning, that the distinction between private planning and public planning is a valid one, but one in need of tweaking. However, the plan–market dichotomy (i.e. the assumption that state and private planning is mutually exclusive) is fallacious. Informed by the neo-institutional economic assumption of rational decisions and the stance of contractual solutions, it rides on the surge in private planning by proposing a taxonomy of planning that combines two modes of planning with two types of planning agent and discusses their possible interrelationships using some neo-institutional economic reasoning informed by the ideas of Coase. Some pedagogical and theoretical implications are also discussed.